Situation Report: Romania, 19 September 1972 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Meeting of County Party Officials US to Aid Romania with Offshore Oil Drilling Manea Manescu in Belgium Romanian-Chinese Relations Party Contacts